The Hays Of Teaching Students To Creative Thinking Through Practical Courses - Niyozali Olimov; Zamira Karimova (Universitas Muhammadiyah Sidoarjo, 2022)
This article describes the problem of increasing the self-activity of the assimilation of knowledge independent thinking by organizing self-education in higher educational institutions.